COMPARISON OF SALBUTAMOL DELIVERED BY METERED DOSE INHALER WITH SPACER VERSUS NEBULIZER IN ASTHMATIC CHILDREN PRESENTING IN PAEDIATRIC EMERGENCY (Journal of Medical & Health Sciences Review, 2025)
Background:  Asthma is one of the most common chronic respiratory diseases in children, often presenting with acute exacerbations requiring prompt management in emergency settings. Salbutamol, a short-acting beta-agonist, is frequently used for rapid bronchodilation, delivered either via nebulization or metered-dose inhaler (MDI) with spacer. While nebulization is a traditional method, MDIs with spacers are emerging as an effective, convenient, and cost-efficient alternative. However, evidence comparing their clinical efficacy in pediatric emergency settings remains limited, particularly in resource-constrained environments.OBJECTIVE: To compare the clinical efficacy of salbutamol administered by metered-dose inhaler with a spacer by nebulizer for the treatment of asthmatic children in emergency.MATERIAL and METHODS:  This Observational analytical comparative study was conducted at the Department of Paediatric Medicine Unit I, King Edward Medical University, Lahore / Mayo Hospital, Lahore, from November 2011 to March 2013.A total of 230 patients (age 5-12y) were included in the study after randomization. They were divided in two groups. In Group-1, 109 patients were included and nebulization technique was used. In Group-2, 111 patients were included and meter dose inhaler with spacer was used. Clinical efficacy was measured at 3hours of treatment. Modified pulmonary index score 20% was achieved; hence both techniques were comparable and effective.  Based on comparative efficacy, simplicity, convenience and financial advantages, meter dose inhalers with spacer can be recommended for use in children with asthma.